Effects of by-products of peach palm and grape on nutritional, physico-chemical and sensory properties of extruded breakfast cereals (Bioscience Journal, 2021)
Extruded breakfast cereals they have low nutritional and high energetic values. The aim of this study was to develop extruded breakfast cereals by replacing part of corn meal by different proportions of by-products of grape (5-10%) and peach palm (7.5-15%). Samples were sweetened with xylitol while moisture was controlled with grape juice. Six formulations, which were produced in a 22 experimental design, were analyzed regarding their composition, besides their technological, mechanical, antioxidant and sensory properties. Addition of different amounts of flours, produced with the wastes of grape (GF) and peach palm (PF), increased the dietary fibers and antioxidant contents of cereals formulations. However, at the highest levels addition, there was a decrease in expansion and an increase in hardness and water solubility properties. Thus, the incorporation of grape and peach palm by-products at smaller proportions showed higher viability, since they exhibited satisfactory sensory acceptance, technological properties and bowl life.